191k views
3 votes
1
(x - 1)/(2x - 4) = (2x - 2)/(3x)2
(3)/(x) + (2)/(x + 1) = \frac{23}{x {}^(2) + x}3
(x + 2)/(2) + 24
(x - 2)/(2) = 4

User Vimukthi
by
4.7k points

1 Answer

7 votes

Find x

(x-1 )/ (2x-4) = (2x -2) / 3x

________________

Can you see the updates?

_________________

(x-1 )* 3x = (2x -2) (2x-4)

x* 3x -1*3x = 2x*2x -2*2x - 4*2x +2*4

3x^2 - 3x = 4 x^2 -4x - 8x + 8

4 x ^2 - 3x^2 -4x + 3x -8x + 8 = 0

x ^2 - 9x + 8

(x -1) (x -8) = 0

x = 1

x = 8

_____________

Answer

x = 1

x = 8

________________

Do you have any questions regarding the solution?

If you do not need further explanation on this question, we can end the session.

I want to remind you this answer will always be saved in your profile. I’d really appreciate you letting me know how I did by rating our session after you exit. Thanks, and have a great day!

User TangoKilo
by
4.5k points